Analysis of Maxillofacial Injuries of Vehicle Passengers Involved in Frontal Collisions - Hitosugi, Masahito; Mizuno, Koji; Nagai, Toshiaki; Tokudome, Shogo (Journal of Oral and Maxillofacial Surgery, 2011)
To clarify the incidence and mechanisms of maxillofacial injuries sustained by motor vehicle passengers, in-depth data from the Institute for Traffic Accident Research and Data Analysis, Japan, were retrospectively analyzed. From the Institute for Traffic Accident Research and Data Analysis in-depth data for 1993 through 2005, data were collected for 226 individuals with maxillofacial injuries who were adult passengers involved in frontal motor vehicle collisions. The accident information, a subject's medical data, and anatomic Injury Severity Scores were examined. The median Injury Severity Score was 2, and the mean equivalent barrier speed of the vehicles was 35.2 ± 13.0 km/hour. The most common maxillofacial injuries were lacerations (46.7%), followed by abrasions (41.9%), fractures (14.0%), and dental injuries (5.7%). Maxillofacial fractures occurred more often in unrestrained drivers without airbag deployment (18.4%) and less often in restrained drivers with airbag deployment (4.3%). The incidences of fractures caused by impacts with areas other than the steering wheel were markedly decreased using any safety device (35.5% to 0%). Combined use of seat belts and airbags by occupants decreases fractures compared with completely unrestrained occupants. Furthermore, wearing a seat belt prevents the free flight of drivers within a vehicle and contact with the interior of a vehicle (other than the steering wheel). Although the anatomic Injury Severity Score of maxillofacial injuries was relatively low, because these injuries are also associated with socioeconomic costs, the correct use of safety devices and further development of more effective injury prevention systems are needed.